2016
DOI: 10.1039/c5cy02274f
|View full text |Cite
|
Sign up to set email alerts
|

Local structures and TWC activity of Pd supported on Ni-substituted aluminium oxide borates

Abstract: The Pd catalyst supported on Ni-substituted aluminum oxide borate (Ni–10A2B) achieved the highest catalytic activity under three-way catalysis conditions, where NO adsorption onto the Ni site promoted the reaction with hydrogen spilt over from Pd under rich conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…: 1950 °C); its crystal structure is described as mullite analogues comprising AlO 6 octahedra, irregular AlO 5 polyhedra, AlO 4 tetrahedra, and planar BO 3 triangles (Supporting Information). The catalytic application of this material was first reported for catalytic CH 4 combustion over Pd/10A2B, and we have studied this for automotive three-way catalysts. , Figure shows the XRD patterns of CuO x /10A2B and CuO x /Al 2 O 3 (Al 2 O 3 : JRC-ALO-8, supplied by Catalysis Society of Japan) as a reference before and after thermal aging at 900 °C for 100 h in air. For as-prepared catalysts, the diffraction peaks of CuO x /10A2B could be assigned to 10A2B and CuO; however, those of CuO x /Al 2 O 3 could be assigned to only γ-Al 2 O 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…: 1950 °C); its crystal structure is described as mullite analogues comprising AlO 6 octahedra, irregular AlO 5 polyhedra, AlO 4 tetrahedra, and planar BO 3 triangles (Supporting Information). The catalytic application of this material was first reported for catalytic CH 4 combustion over Pd/10A2B, and we have studied this for automotive three-way catalysts. , Figure shows the XRD patterns of CuO x /10A2B and CuO x /Al 2 O 3 (Al 2 O 3 : JRC-ALO-8, supplied by Catalysis Society of Japan) as a reference before and after thermal aging at 900 °C for 100 h in air. For as-prepared catalysts, the diffraction peaks of CuO x /10A2B could be assigned to 10A2B and CuO; however, those of CuO x /Al 2 O 3 could be assigned to only γ-Al 2 O 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A wide variety of commercially available metal oxides (Table ) were used as support materials for CuO x . As a support with high performance for NH 3 combustion, aluminum oxide borate (Al 20 B 4 O 36 , 10Al 2 O 3 ·2B 2 O 3 : 10A2B) was prepared by a reverse coprecipitation method. , An aqueous solution containing Al­(NO 3 ) 3 and H 3 BO 3 (Wako Pure Chemicals) with a molar ratio of Al/B = 10:2 was added dropwise to a 3 mol·L –1 solution of (NH 4 ) 2 CO 3 (Wako Pure Chemicals) under vigorous stirring until the pH reached 7.0. The precipitate thus formed was calcined at 500 °C for 3 h and finally at 1000 °C for 5 h in air.…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in CO conversion with the increase in NO conversion indicates that the Ni loading caused the selectivity to change from the CO–O 2 reaction to the CO–NO reaction. It has been reported that the partially oxidized Ni species promote NO adsorption, , indicating that the Ni loading on Cu/Al 2 O 3 promoted NO adsorption when a stream of the stoichiometric NO–CO–C 3 H 6 –O 2 gas mixture was used and accelerated the CO–NO reaction with the decrease in the CO–O 2 reaction. The influence of Ni on the structure of the Cu active sites and catalysis will be discussed later.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Three-way catalysts (TWCs) are employed in state-of-the-art technologies for automotive emission control. The use of platinum group metals (PGMs) deposited on conventional TWCs should be limited owing to their scarcity. Therefore, the development of alternative catalytic materials comprising inexpensive and abundant base metals has attracted extensive attention. Nitrogen oxides (NO x ), carbon monoxide (CO), and unburned hydrocarbons such as C 3 H 6 are the primary constituents of exhaust gas.…”
Section: Introductionmentioning
confidence: 99%
“…Поскольку бор имеет особенность интенсивно выгорать в процессе СВС, то было добавлено его избыточное количество с целью компенсировать выгоревшие потери. Также в системе Al-B-O характерно образование боратов алюминия при высоких температурах, начиная с 900 -950°С [24,25]. При СВС образование боратов происходит за счет взаимодействия оксида алюминия с борсодержащими соединениями.…”
Section: результаты и обсуждениеunclassified